Net profit how to succeed in digital business - Soskin, David, 1954- (Wiley, 2010)
"Online business can be a goldmine - or a minefield. David Soskin, former CEO of Cheapflights and Chairman of mySupermarket.co.uk, has faced all the problems thrown up by building a business on the Internet, and solved them. Here, he shows you how to: Convert a brilliant idea into something that actually pays Get the funding you need to expand Build a great team of staff and advisers Keep the cash flowing Go global! Net Profit provides much needed inspiration and reassurance for would-be start ups and established businesses who want to do more online"--